Implementasi Pendidikan Dari Q.S Al Hujurat Ayat 13 Tentang Litaarafu Dalam Proses Interaksi Pendidik Dengan Peserta Didik - Wardiyah Wardiyah; Lisdaleni Lisdaleni; Dwi Noviani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This article aims to discuss different human conditions, whether in terms of nationality or race or language, this does not mean division, but to get to know each other (ta'aruf). Basically, humans are the same before Allah, the difference is the degree of piety. In the process of socializing and understanding each other, we still have to pay attention to religious teachings, so as not to make unnecessary things happen. In learning interactions, educators and students need to get to know each other more deeply in order to be able to carry out their respective roles, duties and responsibilities well, by knowing themselves, educators can know their strengths and can try to find solutions to improve their weaknesses, and vice versa, students can understand the teacher well, the nature of the teacher, the teacher's habits and other things. In this research, the writing uses a qualitative approach with library research techniques using descriptive analysis. The object used as research is interpretation. The results of the research can be concluded that the essence contained in Q.S Al-Hujurat verse 13, Lita'arafu (ta'aruf) in the Al-Quran surah Al Hujurat verse 13 is not just getting to know each other inside out, but more than that, humans it is also required to know oneself